Determining the Linguistic Profile of Children With Rare Genetic Disorders. - Espinosa-Mojica, Ana Alejandra; Varo, Carmen Varo (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Language studies on populations with rare genetic disorders are limited. Hence, there is little data on commonly found or expected developmental linguistic traits and cognitive mechanisms that may be impaired. Based on the hypothesis that there is a close connection between language and cognition and the relevance of specific genetic changes in the development of each, our goal was to provide linguistic data on relationships with other executive functioning mechanisms. Method: This study assessed language skills, communicative behaviors, and executive functions in four children, aged 7–9 years, with rare genetic disorders, using standardized protocols and tests. Results: The findings revealed different levels of language impairment and executive functioning problems in each case. The overall executive function index performance for each of the four cases studied was clinically significantly high, indicating executive dysfunction. Conclusions: The cases analyzed illustrate different types of atypical development that affect both language and other cognitive mechanisms and underscore the importance of executive skills and the various ways in which they are involved in diverse levels of language that might be affected to a greater or lesser degree in rare genetic disorders. In conclusion, we found that language dysfunction is a salient feature of the rare genetic disorders included in our study, although this is not necessarily true for all genetic disorders. Along with these conclusive results, we performed a qualitative analysis of the linguistic and cognitive components that enable functional communication in order to allow optimal interpretation of the data we have collected, laying the foundations for a more effective therapeutic approach.